(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Beginning with a brief review of the concept of theatricality, the article proposes a conceptualization of "Black theatricalities" through intersecting historical, philosophical, and social perspectives. By examining the interactions between body, memory, and history, the text offers a critical, multidisciplinary analysis of how Black scenic productions serve as forms of resistance. Finally, it discusses two contemporary artistic and cultural practices — voguing and ballroom culture — that generate forms of theatricality which can be understood as Black, with particular attention to how these expressions are embodied in the South African production Nkoli - The Vogue Opera.